Performance of whole blood interferon-γ release assays in SARS-CoV-2 and tuberculosis is age dependent - Rothoeft, Friedrich Tobias Ingo; Hoffmann, Anna Teresa; Maier, Christoph; Denz, Robin; Kobbe, Robin; Friedrichs, Anette; Behrens, Georg Martin Norbert; Behrens, Pia; Berner, Reinhard; Caliebe, Amke; Denkinger, Claudia M.; Giesbrecht, Katharina; et al. (Infection, 2025)
Introduction: A lot of research has been done, mainly on tuberculosis (TB), on the extent to which cellular immune protection as measured by interferon-γ release assays (IGRA) is age-dependent. In a previous study we showed that following an Omicron infection, adolescents with a hybrid immunity had a higher probability of having a reactive SARS-CoV-2-specific IGRA than children. Therefore, we examined in a large group of minors and adults whether age influences cellular immunity as measured by IGRA in TB and SARS-CoV-2. Methods: Participants were recruited at 13 German study sites between September and December 2022. Cellular immunity was analyzed using SARS-CoV-2 and Tb-specific IGRA and humoral immunity against SARS-CoV-2 by measuring antibodies against spike (S) and nucleocapsid protein. Analysis was done depending on natural (convalescent, not vaccinated) or hybrid immunity (convalescent and vaccinated). Results: Overall, 1401 adults and 392 minors were included. The amount of interferon-γ released by T cells, as well as the probability of a positive SARS-CoV-2 IGRA (OR 1.022) and a positive Tb IGRA (OR 1.047) were age dependent. Sensitivity of SARS-CoV-2 IGRA in natural immunity was lower in minors (0.45), especially in those less than 5 years (0.29) as compared to adults (0.66). Conclusion: The interferon-γ response to SARS-CoV-2 infections and/or vaccinations and to Tb infections as measured by IGRA is in quality and quantity dependent on age. The sensitivity of commercially available tests in young children seems to be suboptimal, limiting their use as a diagnostic or research tool in this age group.